2000
DOI: 10.1177/096120330000900716
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism and transitory anti-b2-GPI antibodies in an adult with chicken pox

Abstract: Anti-beta2-glycoprotein I antibodies are considered as a specific marker for the antiphospholipid syndrome. In contrast to lupus circulating anticoagulant and anticardiolipin (aCL) antibodies, they are usually not found at significant levels in infections. We report a case of pulmonary embolism in an adult with varicella. Transient significant levels of aCL antibodies and of IgM anti-beta2-GPI antibodies were observed. No other prothrombotic factor, including free protein S antigen deficiency, was found. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
1
10
0
1
Order By: Relevance
“…The absence of any protein S increase after receiving fresh frozen plasma, the return to normal levels of protein S 1 month after infection as well as the parents’ normal protein S values, all indicate that protein S deficiency was acquired and caused by anti-protein-S antibodies. Moreover, antiphospholipid antibodies were found in this patient as well as in other patients with thrombotic complications and/or purpura fulminans following varicella infection [3, 4, 10, 11]. It is possible that the simultaneous presence of a protein S deficiency and antiphospholipid antibodies concur to explain the severity of the clinical manifestation [4, 12].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of any protein S increase after receiving fresh frozen plasma, the return to normal levels of protein S 1 month after infection as well as the parents’ normal protein S values, all indicate that protein S deficiency was acquired and caused by anti-protein-S antibodies. Moreover, antiphospholipid antibodies were found in this patient as well as in other patients with thrombotic complications and/or purpura fulminans following varicella infection [3, 4, 10, 11]. It is possible that the simultaneous presence of a protein S deficiency and antiphospholipid antibodies concur to explain the severity of the clinical manifestation [4, 12].…”
Section: Discussionmentioning
confidence: 99%
“…An adult patient who suffered a pulmonary embolus during the course of a varicella infection accompanied by transiently elevated levels of aCL and b2GPI has been documented (Viseux et al, 2000). Uthman et al (2001) reported a 16-year-old male who developed an ilio-femoral thrombosis 1 week following a chickenpox infection.…”
Section: Varicella Virusmentioning
confidence: 97%
“…Thrombotic events associated with transient aPL have also been reported in a few cases of varicella-zoster virus (VZV) and Epstein-Barr virus infection [19][20]. Recently, Losurdo et al [21] described two pediatric cases with varicella-associated cerebrovascular disease that had positive IgM anti-2 -GPI antibodies and that became negative after 1 month.…”
Section: Viral Infectionsmentioning
confidence: 99%